2006
DOI: 10.2215/cjn.01120905
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Treatment for Severe Childhood IgA Nephropathy

Abstract: A previous trial showed that treatment of children with severe IgA nephropathy (IgAN) using prednisolone, azathioprine, heparin-warfarin, and dipyridamole for 2 yr early in the course of disease reduced the severity of immunologic renal injury and prevented any increase in the percentage of sclerosed glomeruli. This study compared the effects of prednisolone, azathioprine, warfarin, and dipyridamole (combination) with those of prednisolone alone in 80 children with newly diagnosed IgAN that showed diffuse mesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 24 publications
4
72
0
3
Order By: Relevance
“…Our previous two RCTs and clinical trial showed the short-term effectiveness of combination therapy in childhood IgA nephropathy (5,9,10). To the best of our knowledge, no well-designed RCTs of childhood IgA nephropathy have been performed with the exception of those that we conducted.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous two RCTs and clinical trial showed the short-term effectiveness of combination therapy in childhood IgA nephropathy (5,9,10). To the best of our knowledge, no well-designed RCTs of childhood IgA nephropathy have been performed with the exception of those that we conducted.…”
Section: Discussionmentioning
confidence: 91%
“…Goumenos et al (29) retrospectively reported that treatment with prednisolone and azathioprine appeared to be beneficial in slowing the progression of severe adult IgA nephropathy. We conducted another multicenter prospective RCT comparing combination therapy with prednisolone monotherapy for severe childhood IgA nephropathy (9). The results of this study showed that patients who received prednisolone monotherapy had more sclerosed glomeruli than did those who received combination therapy, although proteinuria was reduced in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…64 In the other trial, azathioprine plus corticosteroids plus anticoagulants were tested against steroids alone. 65 In both cases, the combination therapy led to higher rates of complete remission of proteinuria.…”
Section: Immunosuppressive Combination Therapy Is Not Recommendedmentioning
confidence: 95%
“…In two Japanese trials, both from the same group, 64,65 children with IgAN and severe histologic changes and/or significant proteinuria, yet normal GFR, received azathioprine plus corticosteroids plus anticoagulants versus anticoagulants alone. 64 In the other trial, azathioprine plus corticosteroids plus anticoagulants were tested against steroids alone.…”
Section: Immunosuppressive Combination Therapy Is Not Recommendedmentioning
confidence: 99%
“…However, there is controversy over the efficacy of immunosuppressants. Some low-quality evidence has shown that treatment with glucocorticoids and cyclophosphamide (CTX) or azathioprine in progressive IgAN patients is significantly better than other treatment regimens (21)(22)(23)(24)(25). However, issues of case enrollment, observation bias and lack of better supportive care measures in these patients make these studies difficult to interpret (26).…”
Section: Discussionmentioning
confidence: 99%